Press Freedom Papua Journalist : an Interpretive Phenomenological Studies - Lifita Yiska Tabita Lumenta; Veronika Veronika (Jurnal Spektrum Komunikasi, 2022)
The mass media and Papuan human rights issues are interrelated. In the reporting process, there is one party involved and the most dominant is the journalist profession. Journalists need to prepare themselves and special abilities when they want to cover. Unfortunately, not many people know about the experiences of journalists covering Papuan human rights issues. Therefore, researchers feel that this is important to do to fill the void and increase knowledge. The purpose of this study is to find out how the meaning of the experience journalists in covering and producing news on human rights issues in Papua. This study uses the Phenomenology research method with the flow of Interpretative Phenomenology Analysis (IPA) which is owned by Edmund Husserl. The IPA stream is considered capable of explaining the meaning of experience in detail. Key informants, the researchers chose three journalists who had more than seven to twenty years of experience in covering Papuan human rights issues, with the aim that the information obtained from the informants was broader and deeper. Results The research resulted in three discussion themes. 1) Definition of the journalist profession, namely having to work from the heart, understanding and complying with the Journalistic Code of Ethics, having high ideals, and being able to understand the original character of Papuans; 2) Define self-censorship, namely by having a strong mentality, being brave, informative, and producing news that can be accounted for; 3) Freedom of the press, which is considered very lacking, especially in Papua.